2010
DOI: 10.1021/jf1000293
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Content and Composition of Phenolic Compounds in Permanent Pastures According to Botanical Variation

Abstract: Phenolic compounds contribute to the micronutrient composition of pasture, which in turn may affect animal product composition. To assess the importance and variations in content of these compounds, the polyphenolic and botanical compositions of 24 permanent pastures located in one lowland and two upland regions were studied at equivalent stages of growth. Phenolic fractions were characterized and quantified using HPLC-PDA-ESI-QToF, and the total content was determined by colorimetry over each whole pasture. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
1
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 21 publications
1
32
1
2
Order By: Relevance
“…In the present study, not all analysed plants showed high TPC values. In some species, these levels were similar to or lower than in species from temperate regions: e.g., A. adsencionis, J. dioica, L. dubia and O. streptocantha species had smaller TPC contents (from 0.147 to 0.189 g of GAE · kg -1 ) than three mixtures of French pasture plants that averaged 9.5 g of GAE · kg -1 (Reynaud et al, 2010). Dudonné et al (2009) reported that the concentration of total phenolic compounds in 30 aqueous plant extracts ranged from 6.86 to 397.03 mg GAE · g -1 of sample measured by the Folin-Ciocalteu method, meanwhile we found values from 77 to 38170 mg GAE · kg -1 of sample DM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, not all analysed plants showed high TPC values. In some species, these levels were similar to or lower than in species from temperate regions: e.g., A. adsencionis, J. dioica, L. dubia and O. streptocantha species had smaller TPC contents (from 0.147 to 0.189 g of GAE · kg -1 ) than three mixtures of French pasture plants that averaged 9.5 g of GAE · kg -1 (Reynaud et al, 2010). Dudonné et al (2009) reported that the concentration of total phenolic compounds in 30 aqueous plant extracts ranged from 6.86 to 397.03 mg GAE · g -1 of sample measured by the Folin-Ciocalteu method, meanwhile we found values from 77 to 38170 mg GAE · kg -1 of sample DM.…”
Section: Discussionmentioning
confidence: 99%
“…The intake of specific plants and particular food items is regulated by the availability of the desired food and the capability of grazers to ingest and digest it (Reynaud et al, 2010;Villalba et al, 2010). Palatability, poisonous threshold, and the presence of alternative food choices are complementary causes that alter grazing behaviour; e.g., it is argued that plant bioactive compounds (PBC) modify animal behaviour and forage selection to maintain rumen functioning aimed at avoiding intoxication or metabolic disorders (Villalba et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liver and plasma antioxidant status of grass-fed lambs Marais et al, 2000;Regos et al, 2009;Reynaud et al, 2010), therefore it would be interesting to evaluate whether feeding of forage legumes would lead to larger antioxidant effects in the lamb tissues. The chromatogram of the grass sample (Supplementary Figure S1a) showed only few peaks and with relatively low intensities between 5 and 13 min.…”
Section: Discussionmentioning
confidence: 99%
“…Apigenin, luteolin (flavones) and quercetin (flavonol) belong to a large group of phenolic constituents that are extensively distributed in plants present in ruminant diet Reynaud et al, 2010). The structure of flavonoids is based on a common three-ring nucleus containing two benzene rings (A and B) linked via a heterocyclic pyrone ring (C) (Figure 1).…”
Section: Introductionmentioning
confidence: 99%